ANALISIS EFISIENSI PEMASARAN JAGUNG KUNING DI KECAMATAN BONTOLEMPANGAN KABUPATEN GOWA - Muhammad Yahya (AkMen JURNAL ILMIAH, 2009)
Problems which wish checked by is how big storey; level of efficiency of maize marketing yellow pursuant to to the number of marketing institute in concerned in Subdistrict of Bontolempangan of Regency Gowa, while target which wish reached in this research is to know the level of storey level of efficiency of maize marketing yellow in Subdistrict of Bontolempangan of Regency Gowa. As for hypothesis that is anticipated by that marketing efficiency of at every marketing institute show the difference Awaking analysis which have been conducted by researcher got by that most efficient marketing channel of marketing expense is channel of III assess 6,84 %, at this marketing channel is direct retailer buy at farmer. Channel II assess the its marketing expense efficiency equal to 9,31 % caused by some marketing institute in concerned, that way also at channel of marketing I with the value of efficiency of marketing expense 12,35